Bernard Lonergan an introductory guide to Insight - Tekippe, Terry J. (New York : Paulist Press, 2003)
"Bernard Lonergan's insight, one of the great philosophical works of the twentieth century, is a challenging book for any reader. Bernard Lonergan: An Introductory Guide to Insight provides readers with a first reading guide, emphasizing what is truly essential and central to Lonergan's work. It allows readers to make their way through a first reading by providing a summary of each chapter and questions for reflection."--BOOK JACKET.
Introduction: Some Practical Pointers -- Ch. 1. Getting One's Bearings -- Ch. 2. Appropriating Insight Through Examples -- Ch. 3. Looking for Insights in All the Right Places -- Ch. 4. What Does Science Know About Knowing? -- Ch. 5. Let's Use Some Common Sense! -- Ch. 6. Jekyll and Hyde of Human Knowing -- Ch. 7. You Have to Be Judgmental! -- Ch. 8. How Does One Become a Person of Good Judgment? -- Ch. 9. Suiting the Action to the Word -- Ch. 10. If I'm a Knower, What Do I Know? -- Ch. 11. True Objectivity Is Authentic Subjectivity -- Ch. 12. Can Knowing Reveal the Metaphysical Structure of Being? -- Ch. 13. So What Is the Structure of the Known? -- Conclusion: Retrospect and Prospect.
Includes index.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Lonergan, Bernard J. F; Knowledge, Theory of; Lonergan, Bernard J. F; PHILOSOPHY / Epistemology; Electronic books